Effect of Concentation and Duration of Colchicine on Survival Rate and Cell Characteristic of Dendrobium chrysotoxum Lindl. Protocorm - อติชาติ พรทิพย์ (KKU Science Journal, 2014)
This research was conducted to study survival rate and cell characteristic of Dendrobium chrysotoxum after treated with colchicine. The protocorms were submerged in various concentrations of colchicines (0, 0.01, 0.02, 0.03, 0.04 and 0.05 %) for 1, 2, 3, 4 and 5 days. The survival rate, chrolophyll content and size of parenchyma cell were evaluated after two months of the culture on Vacin and Went (1949) medium. It was found that higher concentration of colchicine and longer treatment duration reduced protocorm survival. Chrolophyll content of treated protocorms were higher than the control. The treated protocorms with 0.03% colchicine for 1 day provided the largest parenchyma cell (107.77±6.08 µm in diameter). Whereas the largest size of parenchymatous nucleus could be observed when protocorms were treated with 0.05% colchicine for 2 days.